Implementation of Odoo-Based ERP in The Case Study of Micro, Small, and Medium Enterprises(MSME) "Woody Moody Jakarta" - Syafitri Lutfia Zahra Zahra; Teddy Siswanto; Syaifudin (Intelmatics, 2023)
Woody Moody is a Micro, Small, and Medium Enterprises (MSME) engaged in custom furniture services and is currently growing in West Jakarta. The operational business processes are still manually managed, starting from orders to transactions, resulting in manual handling of data related to sales results and transaction reports using spreadsheets. By implementing the Odoo methodology, an integrated Enterprise Resource Planning (ERP) system can help the MSME address existing issues in their business processes.The implementation of the integrated Enterprise Resource Planning (ERP) system aims to accommodate specific information system needs and assist in streamlining the business processes, starting from order processing to sales, thereby ensuring effective and efficient transactions. The results of the implementation demonstrate that the open-source Odoo-based Enterprise Resource Planning (ERP) can resolve these issues through the integration of digital business processes, providing convenience for business owners. Index Terms— ERP, Odoo, UMKM, Integration